The Influence of Motivation and Work Culture on Employee Performance in Supporting The Achievement of SDG’S 2 & 3 (Zero Hunger, Healthy and Prosperous Life) - Indriasari, Fika; Efani, Anthon; Badriyah, Nurul; Tiarantika, Reny (Graduate School Universitas Brawijaya, 2026)
The achievement of Sustainable Development Goals (SDGs), particularly Goal 2 (Zero Hunger) and Goal 3 (Good Health and Well-Being), relies heavily on the performance of civil servants in delivering public services. This study examines the effects of work culture and work motivation on ASN performance and their contribution to sustainable development in Malang City. A quantitative approach was employed, using Structural Equation Modeling–Partial Least Squares (SEM-PLS) 4.0, with a stratified random sample of 100 ASN from sub-district offices and community health centers. Results indicate that work culture positively influences civil servants' performance (? = 0.449; p < 0.001) and SDG achievement (? = 0.433; p < 0.001). Work motivation also exerts a positive effect on performance (? = 0.339; p < 0.001) and SDGs (? = 0.363; p < 0.001). ASN performance significantly contributes to sustainable development (? = 0.290; p = 0.002) and mediates the relationship between work culture and SDGs (indirect effect = 13%) and between motivation and SDGs (indirect effect = 9.8%). These findings demonstrate that fostering a strong work culture and high motivation among civil servants directly and indirectly enhances sustainable development outcomes, providing empirical evidence linking civil servant performance to local SDG implementation. Keywords: Work Culture, Work Motivation, Performance, ASN, SDGs